Prepare for the Accuplacer Test with our comprehensive quiz. Find practice questions, tips, and resources to help you succeed.

Practice this question and more.


When x=3, y=-4, and z=2, what would be the solution for equation 8 - 4(x - 1) = 2 + 3(4 - x)?

  1. -2

  2. 0

  3. 2

  4. 4

The correct answer is: -2

To find the solution for the equation 8 - 4(x - 1) = 2 + 3(4 - x) when x=3, y=-4, and z=2, we first substitute the value of x (which is 3) into the equation. Starting with the left side of the equation: 8 - 4(3 - 1) simplifies to: 8 - 4(2) = 8 - 8 = 0. Now, let's evaluate the right side: 2 + 3(4 - 3) simplifies to: 2 + 3(1) = 2 + 3 = 5. Now we can compare the simplified left side (0) with the right side (5). Since both sides are not equal, we need to understand what the question is asking which is to evaluate the expression rather than verify the equality. Therefore, if we evaluate both sides separately as an expression based on the value of x, the final answer can be misleading if not calculated correctly. The true operations show that the simplification needs a close observation. The evaluation shows that none of the given answers (including -2) satisfy the evaluation of the entire equation, and the true